Tumor microRNA-126 controls cell viability and associates with poor survival in patients with esophageal adenocarcinoma. Issue 14 (October 2019) - Toxopeus, ELA; Lynam-Lennon, N; Biermann, K; Dickens, G; de Ruiter, PE; van Lanschot, JJB; Reynolds, JV; Wijnhoven, BPL; O'Sullivan, J; van der Laan, LJW
Esophageal adenocarcinoma displays a poor prognosis and current treatments are often not curative. Pathological TNM-stage is a prognostic parameter, but a better understanding of the pathophysiology of esophageal adenocarcinoma is needed to better predict survival. Recent work in other malignancies indicated an important role for the regulator microRNA-126 (miR-126) in tumors. The aim of this study was to investigate the function of miR-126 in esophageal adenocarcinoma and to correlate expression of miR-126 with tumor cell behavior and patient survival. Functional assays were performed in esophageal adenocarcinoma cell lines (OE33) in vitro by overexpressing or antagonizing miR-126 and assessing cellular processes linked to the hallmarks of cancer. In vivo pre-treatment biopsies of 58 patients with esophageal adenocarcinoma who underwent neoadjuvant chemoradiotherapy and surgery were analyzed for miR-126 expression in tumor cells by qRT-PCR and patient survival was analyzed by Kaplan–Meier and Cox regression. In OE33 cancer cells, stable overexpression of miR-126 modest though significantly altered expression of genes related to cell death (MEK1) and DNA repair (POLB and TERF1) was observed. Also the secretion of the angiogenic and pro-inflammatory factors, VEGF, IL-1β, and IL-6 were regulated by miR-126 ( P  < 0.029). Importantly, miR-126 was found to be a regulator of cell viability in OE33 cells. Overexpressing ( P  = 0.043) and antagonizing ( P  = 0.035) miR-126 showed reciprocal effects on tumor cell viability and significantly regulated expression of pro- and anti-apoptotic genes, TP53, and GATA6 ( P  < 0.031). In patients, high levels of miR-126 expression in pre-treatment tumors were significantly associated with poor survival ( P  = 0.031). In multivariable analysis, high miR-126 ( P  = 0.038) together with ypN-stage ( P  = 0.048) were shown to be independent risk factors for poor survival. In conclusion, high expression of miR-126 in esophageal adenocarcinoma prevents tumor-cell death and is associated with poor patient survival. This study warrants further analysis of miR-126 as biomarker or potential therapeutic target for OAC. Impact statement: Esophageal adenocarcinoma is a common form of cancer of the esophagus. It has an increasing health impact as it is associated with very poor patient survival. A better understanding of the pathophysiology of this cancer is needed to identify better treatment strategies and to provide a better prognosis for these patients. MicroRNAs have emerged as important molecular regulators of cancer cell viability and proliferation. The aim of our study was to investigate the role of one very well established microRNA, miR-126, in esophageal adenocarcinoma. Our research shows clear experimental evidence that miR-126 controls cell viability of esophageal adenocarcinoma cells. High (over)expression of miR-126 increased the viability of these cells. Our preclinical data were shown to be clinically relevant for this field of oncology. In an independent validation study of esophageal adenocarcinoma biopsies, we confirmed that high miR-126 expression in tumor cells was an independent risk factor for poor patient survival.